The association between adverse events and outcome under checkpoint inhibitors: Where is the deal? - Gerard Milano; Federico Innocenti; Joseph Ciccolini (Translational Oncology, 2021)
Recent reports have put into evidence the possibility of a link between immune-related adverse events (IRAEs) and treatment outcome, patients drawing a benefit from treatment being also exposed to the risk to develop toxicity.A still unanswered question remains the biological origin(s) which can sustain and explain such a relationship.The purpose of this review paper is to lay out different potential contributions which can help to understand the IRAEs-outcome link and to propose clinical perspectives taking advantage of this association.In this respect, pharmacokinetics aspects, immunological and immunogenetics implications have been taken into consideration.